Pendekatan Model Causal Loop Diagram (CLD) Pada Pengelolaan Air Limbah PT.Chandra Asri Petrochemical - Prastyo, Thomas; Sajidah, Hana; Nabilah, Ismi; Sahrupi, Sahrupi (Fakultas Teknik Universitas Tulang Bawang, 2024)
The development of industries linked to population growth in Indonesia has led to increased waste production, particularly in terms of wastewater. This research examines the wastewater management system at PT. Chandra Asri Petrochemical Tbk (CAP), emphasizes the importance of waste treatment to prevent environmental pollution and maintain ecosystem sustainability. Through literature review methods, field studies, and the utilization of a simulation model employing Causal Loop Diagrams (CLD), this study evaluates the impact of industrial wastewater management on the environment and society. The research findings identify wastewater treatment processes at CAP, including the Neutralization Pit, Oil Separator, Dust Filter, and Dust Trap, along with regular inspections to ensure that water quality meets the established standards. Keywords: Causal Loop Diagrams, Dynamic Methods, Environmental Impact, Waste Water Quality Standards, Waste Water Treatment.